Irrigating agriculture with information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
regional workshop on 'Agricultural information needs for West African Countries'. The workshop was jointly organized by CTA and the Economic Community of West African States (ECOWAS) and took place between 11-14 May 1993 Banjul, the Gambia.